1994
DOI: 10.1111/j.1574-6976.1994.tb00144.x
|View full text |Cite
|
Sign up to set email alerts
|

Notes on protozoa in agricultural soil with emphasis on heterotrophic flagellates and naked amoebae and their ecology

Abstract: Heterotrophic flagellates and naked amoebae are usually very numerous in agricultural soils; with numbers in the magnitude of 10,000 to 100,000 (active+encysted) cells per gram of soil. In 'hotspots' influenced by living roots or by dead organic material, the number may occasionally be as high as several millions per gram of soil. An exact enumeration of these organisms is virtually impossible. As they most often adhere closely to the soil particles, direct counting will underestimate numbers since the organis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
95
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 220 publications
(102 citation statements)
references
References 170 publications
2
95
0
Order By: Relevance
“…Protist numbers in the unpolluted control soil (Lara et al, 2007b) were reported to be in general at the lower end of what is usually found in soils (Ekelund and Rønn, 1994), which we attribute to the low organic carbon content (0.04%) in the control soil. However, we cannot exclude that a second round of PCR amplification may increase differential amplification in complex template mixtures and thus influence the abundance of a sequence type in a DGGE gel (Suzuki and Giovannoni, 1996).…”
Section: Evaluation Of the Semi-nested Dgge Protocolmentioning
confidence: 45%
“…Protist numbers in the unpolluted control soil (Lara et al, 2007b) were reported to be in general at the lower end of what is usually found in soils (Ekelund and Rønn, 1994), which we attribute to the low organic carbon content (0.04%) in the control soil. However, we cannot exclude that a second round of PCR amplification may increase differential amplification in complex template mixtures and thus influence the abundance of a sequence type in a DGGE gel (Suzuki and Giovannoni, 1996).…”
Section: Evaluation Of the Semi-nested Dgge Protocolmentioning
confidence: 45%
“…the ratio of total microbial biomass to basal respiration of the active biomass) has been found to be increased [2,10,79]. Protozoa are considered to be effective bacterial predators because of their high turnover rates and high numbers in rhizosphere soil [34,42,135]. Thus, concomitant with an increase in microbial turnover in the presence of microfauna [2,31,32] grazing on microflora may result in a decrease in bacterial numbers.…”
Section: Microbial Activity In the Rhizospherementioning
confidence: 99%
“…Between them, the architecture of the habitable soil pore network which is determined by soil texture and structure, and the moisture in the soil have considered as the two most important factors in the regulation of soil protozoan populations. Their interaction establishes the basic environmental surrounding for soil sarcodina [12]. However, little research has been reported about the effect of multi-physicochemical-factors on sarcodina abundance, though the effects of single-physicochemical-factors of soil parameters such as soil moisture, pH, OM and nutrition salt (TN, TP and TK) on sarcodina abundance have been reported to some extent [20,24,26].…”
Section: Relationship Between Sarcodina Abundance and Soil Physicochementioning
confidence: 99%
“…This accords with other terrestrial regions of the world [4,13,22,28], though their dominant species were different. Ekelund and Rønn [12] considered that testate amoebae are K-selected; whereas, most other Protozoa (smaller naked amoebae and flagellates for example) are r-selected, especially the groups that feed on bacteria. This Kselection may enable testate amoebae to adapt to the permanent drought climate of general terrestrial soils and helps to explain why testate amoebae are the first dominant group of the sarcodina in our analyses.…”
Section: Sarcodina Community Compositionmentioning
confidence: 99%